2019
DOI: 10.5194/acp-19-6295-2019
|View full text |Cite
|
Sign up to set email alerts
|

Cloud droplet growth in shallow cumulus clouds considering 1-D and 3-D thermal radiative effects

Abstract: Abstract. The effect of 1-D and 3-D thermal radiation on cloud droplet growth in shallow cumulus clouds is investigated using large eddy simulations with size-resolved cloud microphysics. A two-step approach is used for separating microphysical effects from dynamical feedbacks. In step one, an offline parcel model is used to describe the onset of rain. The growth of cloud droplets to raindrops is simulated with bin-resolved microphysics along previously recorded Lagrangian trajectories. It is shown that therma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 49 publications
0
21
0
Order By: Relevance
“…Even in the absence of biases horizontal photon transport will lead to a differential heating of the cloud. In idealized large-eddy simulations this effect has been shown to be important for the cloud field development (Jakub and Mayer 2017;Klinger et al 2017;Klinger et al 2019). Whether these effects substantially distort the representation of the cloud field in less idealized situations, and how to capture these effects in parameterizations,…”
Section: Fig 22mentioning
confidence: 99%
“…Even in the absence of biases horizontal photon transport will lead to a differential heating of the cloud. In idealized large-eddy simulations this effect has been shown to be important for the cloud field development (Jakub and Mayer 2017;Klinger et al 2017;Klinger et al 2019). Whether these effects substantially distort the representation of the cloud field in less idealized situations, and how to capture these effects in parameterizations,…”
Section: Fig 22mentioning
confidence: 99%
“…The aforementioned problem is called ''the condensation coalescence bottleneck'' (Brewster 2015;Wang and Grabowski 2009). Previous attempts to pass the bottleneck and simulate more realistic droplet distributions investigated the role of giant cloud condensation nuclei (GCCN) (Feingold et al 1999;Houghton 1938;Johnson 1982;Yin et al 2000), turbulence (Fouxon et al 2002;Grabowski and Wang 2013;Pinsky and Khain 1997) and radiation (Brewster 2015;Guzzi and Rizzi 1980;Klinger et al 2019;Lebo et al 2008; Marquis and Harrington 2005;Rasmussen et al 2002;. We would like to highlight the often underrepresented role of radiation in the diffusional growth process in combination with turbulence.…”
Section: Introductionmentioning
confidence: 99%
“…The thermal radiative cooling is only relevant near the cloud edges, because at the cloud center the emitted radiation is in balance with the absorbed radiation. The distance from the cloud edges at which cooling is relevant depends on the liquid water path and ranges from 50 to 100 m (Klinger and Mayer 2016). The implementation details of the parcel model are based on Grabowski and Abade (2017).…”
Section: Introductionmentioning
confidence: 99%
“…This horizontal transport of radiation causes enhanced cloud top cooling and additional cloud side cooling, so‐called 3D effects, in the thermal spectral range. These 3D thermal heating rates can be as high as several hundred K day 1 (Kablick et al, ; Klinger & Mayer, ) and have been shown to modify cloud circulation and cloud field organization (Guan et al, ; Klinger et al, , ) of shallow cumulus clouds.…”
Section: Introductionmentioning
confidence: 99%